Community Participation in General Elections: Study in Malang City - Klara Kumala Sari; Ali Hanafiah; Mochamad Chazienul Ulum (University of Merdeka Malang, 2024)
Political participation refers to the active involvement of individuals or groups in political activities, such as electing state leaders and influencing government policies. This study focuses on the participation of voters in regional head elections, specifically those who cast their votes incorrectly. The form of political participation under scrutiny is community involvement in general elections. The objective of this research is to examine the nature of community participation in general elections in the city of Malang, Indonesia. This study employs a qualitative descriptive approach, utilizing interview techniques to gather data. It also adopts a case study method to provide an in-depth analysis of the specific instances of political participation in Malang. The research process involved qualitative analysis of data sourced from various libraries. Data and library sources were accessed using online search tools such as Mendeley, Zotero, Publish or Perish, and Google Scholar. These platforms provided access to a wide range of journals, including those on the Scopus platform, ScienceDirect, and other supporting journals. The findings of this research indicate that the model of political participation employed in Malang is of a conventional nature. There has been a noticeable increase in voter turnout in general elections in the city, suggesting a growing level of political engagement among the community. In conclusion, this study provides valuable insights into the nature and extent of political participation in the city of Malang, highlighting the importance of community involvement in shaping the political landscape. It underscores the need for further research to understand the factors influencing voter behavior and to develop strategies to enhance political participation.